Real‐Time Ambulatory ECG Does Not Expedite Care - Melissa Feuerborn; Michael Torre; Ann Lyons; Thomas Jared Bunch; Benjamin A. Steinberg (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Ambulatory ECG (AECG) monitoring is pivotal to the diagnosis of arrhythmias and can be performed with near “real‐time” notification of abnormalities. There are limited data on the relative benefit of real‐time monitoring compared with traditional Holter monitoring. Methods and Results This is a retrospective observational analysis of University of Utah Health patients who underwent ambulatory ECG studies from 2010 to 2022. The study cohort was stratified by patients with an ambulatory ECG that provides real‐time event notification (non‐Holter) versus those who do not (Holter). The outcomes were cardiac implantable electronic device procedure, ablation procedure, emergency department/hospitalization visit, and initiation of anticoagulation out to 6 months. We identified 20 259 patients, 16 650 with non‐Holter studies and 3609 with Holter studies. Holter patients were younger (mean 52 versus 55, P<0.001), more often women (60.2% versus 57%, P<0.001), and had lower mean CHADS2‐VA2Sc scores (1.7 versus 2.1, P<0.001). The median time to ablation procedure was 74 versus 72 (P=0.5), for Holter versus non‐Holter, respectively. Median days to new cardiac implantable electronic device implantation was 54 days versus 52 (P=0.6); initiation of anticoagulation among patients not already treated was 42 versus 31 days (P=0.03). Time to first emergency department visit or hospitalization was 63 versus 57 (P=0.6). In multivariable models, there were no significant differences in time to intervention between Holter and non‐Holter for each outcome. Conclusions Real‐time monitoring demonstrates mixed results in terms of reducing time to intervention, with the significant benefit limited to oral anticoagulation initiation. It is time to revisit clinical scenarios where real‐time ambulatory monitoring may not improve health care efficiency.